Effect of Diacerein on Metabolic Control and Inflammatory Markers in Patients with Type 2 Diabetes Using Antidiabetic Agents: A Randomized Controlled Trial. (2nd April 2018) - Tres, Glaucia S.; Fuchs, Sandra C.; Piovesan, Fabiana; Koehler-Santos, Patricia; Pereira, Fernanda dos S.; Camey, Suzi; Lisboa, Hugo K.; Moreira, Leila B.
Abstract : Introduction. Studies have shown that T2DM is an inflammatory disease. Thus, the present study was aimed at evaluating whether diacerein could improve the metabolic and inflammatory profile among patients with T2DM under long-term treatment with glucose-lowering agents. Methods. This is a double-blind, parallel, placebo-controlled trial with 72 participants randomly assigned to diacerein 50 mg or placebo for 12 weeks. The primary endpoint was the between-group difference in change in HbA1c. Secondary endpoints included the proportion of patients achieving metabolic control [H b A 1 c ≤ 7.0 % (53 mmol/mol)] and change in inflammatory mediators. Results. Participants in the diacerein group had greater reductions in mean HbA1c level in comparison to placebo (−0.98; 95% CI: −2.02 to 0.05, P = 0.06 ), independently of confounding factors. The difference in HbA1c level was −1.3 (95% CI: −2.3 to −0.4) in favor of diacerein (P = 0.007 ) in those with <14 years of diabetes duration versus 0.05 (−0.7 to 0.8;P = 0.9 ) in those with longer duration. The diacerein group had a 50% increase in the number of participants at the lowest TNF- α level (≤1.46 pg/mL). Conclusions. In patients with long-established T2DM under long-term treatment with glucose-lowering agents, diacerein improves metabolic control as measured by HbA1c level and has a favorable impact on inflammatory profile. Clinical Trial Registry. This trial is registered with Brazilian Clinical Trials Registry (ReBEC) numberRBR-29j956 .